"Lydiate is now our home of a sort": perceptions of place amongst ageing first-generation Malawian migrants in Zimbabwe. Issue 3 (3rd July 2022) - Bhanye, Johannes
Abstract : The notion of "home" amongst the diaspora is complex, with some scholars asserting that home in the diaspora is not singular or exclusionary but that migrants are torn between multiple "homes." Other scholars highlight that it is not always the case that migrants in the diaspora have a multiple, plurilocal, constructed perception of home. It can also happen that migrants in the diaspora maintain boundedness, fixity and nostalgic exclusivity in a physical manner when they are estranged from their original homeland. This is often so with ageing, long-term, first-generation migrants, as demonstrated by the current ethnographic study amongst the Malawian diaspora in the Lydiate informal settlement in Zimbabwe. In this perplexing situation, the migrants cling to the ethnic grouping of "Malawian migrants at Lydiate" in an attempt to salvage a measure of community belonging and to help them experience a "home of a sort." The study demonstrates that it is not always the case that ideas of home are shifting, mobile and whimsical; in some instances, often when migrants are ageing and of the first generation, the idea of a stable, sedentary, bounded and fixed perception of home might prevail. In other words, ideas of home are replicated in concentrated imaginings in the "new" country of residence.